Proceedings of the ACM 2012 Conference on Computer Supported Cooperative Work 2012
DOI: 10.1145/2145204.2145354
|View full text |Cite
|
Sign up to set email alerts
|

Collaboratively crowdsourcing workflows with turkomatic

Abstract: Preparing complex jobs for crowdsourcing marketplaces requires careful attention to workflow design, the process of decomposing jobs into multiple tasks, which are solved by multiple workers. Can the crowd help design such workflows? This paper presents Turkomatic, a tool that recruits crowd workers to aid requesters in planning and solving complex jobs. While workers decompose and solve tasks, requesters can view the status of worker-designed workflows in real time; intervene to change tasks and solutions; an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
190
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(191 citation statements)
references
References 16 publications
1
190
0
Order By: Relevance
“…• Anand Kulkarni and his colleagues 6 crowdsource article writing (an article about the attractions of New York City) that involves tasks like structuring an article, writing narrative, splitting content into sections, adding pictures, iterating over content, and coordinating workers that write, correct, or structure text.…”
Section: Crowdsourcing Processesmentioning
confidence: 99%
“…• Anand Kulkarni and his colleagues 6 crowdsource article writing (an article about the attractions of New York City) that involves tasks like structuring an article, writing narrative, splitting content into sections, adding pictures, iterating over content, and coordinating workers that write, correct, or structure text.…”
Section: Crowdsourcing Processesmentioning
confidence: 99%
“…Kulkarni et al proposed a framework to decompose complex tasks into micro-tasks [ 16]. They showed that even the work of decomposing the complex tasks into simple tasks could be crowd-sourced.…”
Section: Related Workmentioning
confidence: 99%
“…14,15 Designing workf lows for complex tasks greatly affects outcome quality. 1,2,5 For instance, one study demonstrated that designing a poor outline for an essay that the crowd will write can result in a low-quality essay.…”
mentioning
confidence: 99%